(untitled) (American Journal of Technology and Applied Sciences, 2024)
This article is in accordance with ISO 3005, ISO 7771, ISO 3759, testing for dimensional change after washing, dry cleaning, soaking and steaming. It also includes learning how to make, mark and measure textiles and clothing. The method used in this article is described as applicable to fabrics, knitted fabrics and finished textiles.